Customer Satisfaction towards Paragliding Services in Pokhara: The Moderating Role of Gender - Thapa Magar, Bikash; Lamichhane, Deennath (Janapriya Journal of Interdisciplinary Studies, 2020)
Customer satisfaction is an important aspect of successful business. So, every business should maintain a good relationship with its customers to enhance loyalty and increase profit. This research considers ‘gender’ as a moderator in the causal relationship between service quality/ value dimensions and overall satisfaction of customers in paragliding through measurement of perceived service quality and perceived service value by applying descriptive and analytical methods. Perceived service quality is measured by the constructs: Reliability, Assurance, Tangibility, Empathy, and Responsiveness while perceive service value is measured by the constructs: Price, Scenery, and Thrill. The landing site near Phewa Lake was chosen as the study area. A convenient sample of 150 respondents was selected for the study. Questionnaire was constructed to elicit primary data on independent variables and was evaluated on fivepoint Likert Scale. Focused group discussions supplemented the study. Gender-wise mean score of different variables revealed that the contribution of perceived service quality to customer satisfaction is higher than that of perceived service value for both the genders. Among the three significant variables- Reliability, Price, and Thrill, the Reliability has higher contribution in Perceived Service Quality measurement. Similarly, the Price has higher contribution in Perceived Service Value Measurement. Overall, the gender-wise level of satisfaction in paragliding among customers is found good. Further studies are needed to establish causal relationship between customer satisfaction and other demographic variables.